#TITLE_ALTERNATIVE# - FITRA SARI (NIM 10104077), AYU
Low-Tension Flood is one of Enhanced Oil Recovery methods for reducing interfacial tension (IFT) between oil and water with the use surfactant. This process will push the oil in the pores reservoir to the production well. The objective of this final project is to measure the potential of Low-Tension Flood with surfactant injection by predicting the displacement e±ciency. Buckley-Leverett continuity equation in one dimensional is being used here. The calculation of front saturation at the shock position is an important for calculating the displacement efficiency . Because Low-Tension Flood involves surfactant as an injection fluid, two shocks front saturation will occur in the process. Those are the water shock front saturation and the surfactant shock front saturation. Those shock front saturations can be calculated from fractional flow curves, which describe water shock front saturation Sorw and surfactant shock front saturation Sorc. Displacement efficiency at the surfactant shock front saturation depends on the concentration of surfactant. The simulation of the displacement efficiency is done in X field. Numerical simulations with X field data show that the displacement efficiency is 68.3% when the water shock front saturation occurs, and for the corresponding the concentration of surfactant 1.5wt%, the displacement efficiency is 81.7% when the surfactant shock front saturation occurs.